FAKTOR – FAKTOR YANG MEMPENGARUHI PURCHASE INTENTION KONSUMEN MUSTIKA RATU DI DKI JAKARTA - Stefanie Angelina; Rodhiah (ITB AAS Indonesia Surakarta, 2025)
This study aims to empirically examine the effect of Social Media Marketing, Brand Awareness, Brand Involvement, and Brand Trust on Purchase Intention. The population in this study were Mustika Ratu consumers in DKI Jakarta. This study used a sample with a non-probability sampling method using convenience sampling technique. The sample size used was 219 people. The data collection technique was carried out online by distributing questionnaires using Google Form. The data obtained was analyzed using SEM PLS through SmartPLS software version 4.1. The results of this study indicate that Social Media Marketing, Brand Awareness, Brand Involvement, and Brand Trust have a positive and significant influence on Purchase Intention. Keywords: Social Media Marketing, Brand Awareness, Brand Engagement, Brand Trust, Purchase Intention.